2013
DOI: 10.1086/674749
|View full text |Cite
|
Sign up to set email alerts
|

First Successful Lung Transplantation for Sickle Cell Disease with Severe Pulmonary Arterial Hypertension and Pulmonary Veno‐Occlusive Disease

Abstract: Abstract:Little is known about the use of lung transplantation in the management of sickle cell diseaseassociated pulmonary arterial hypertension (SCD-PAH). We present clinical and pathological data and report the first successful outcome of bilateral lung transplantation in a patient with severe SCD-PAH and pulmonary veno-occlusive disease (PVOD). We discuss the complexities of multidisciplinary planning and management of lung transplantation in patients with SCD-associated pulmonary vascular complications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The explanted lung of a SCD patient with precapillary pulmonary hypertension was reported to show histopathologic features of pulmonary arterial hypertension, CTEPH, and pulmonary venous obstructive disease. 22 …”
Section: Pulmonary Hypertension-its Classification and Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The explanted lung of a SCD patient with precapillary pulmonary hypertension was reported to show histopathologic features of pulmonary arterial hypertension, CTEPH, and pulmonary venous obstructive disease. 22 …”
Section: Pulmonary Hypertension-its Classification and Pathologymentioning
confidence: 99%
“…The patient was maintained with a hemoglobin S percent ,10% after transplant through exchange blood transfusion. 22 BLOOD, 18 FEBRUARY 2016 x VOLUME 127, NUMBER 7 PULMONARY HYPERTENSION IN SCD 825…”
Section: Postcapillary Pulmonary Hypertension and Left Ventricular Dymentioning
confidence: 99%
“…(8,19,79) Indeed, new studies have found that TSP1, via CD47, limited nitric oxide-mediated vasodilation of distal pulmonary arteries from healthy and end-stage PH lungs. (66) The finding that lungs explanted from patients with PH, (8) including a patient with SCD-associated PH, (23,68) had upregulated TSP1 and CD47 in pulmonary artery smooth muscle cells vessels and parenchyma, also supports the notion that TSP1 may play a pathogenic role in SCD-associated PH. (64) CD47 is also expressed in human and murine RBC, potentially contributing to RBC adhesion to the vascular wall.…”
Section: Introductionmentioning
confidence: 65%
“…PCH is a vascular proliferation of the septal capillaries, described in association with pulmonary veno‐occlusive disease as a rare cause of PH (Montani et al , ). George et al () described the lungs of a single transplanted patient with SCD, describing pulmonary veno‐occlusive disease but no PCH. Focal PCH‐like lesions have been described in several conditions other than in association with pulmonary veno‐occlusive disease.…”
Section: Discussionmentioning
confidence: 99%